I can feel it moving: Science Communicators Talking About the Potential of Mid-Air Haptics - Hajas, Daniel; Ablart, Damien; Schneider, Oliver; Obrist, Marianna (Frontiers in Computer Science, 2020)
We explored the potential of haptics for improving science communication, and recognized that mid-air haptic interaction supports public engagement with science in three relevant themes. While science instruction often focuses on the cognitive domain of acquiring new knowledge, in science communication the primary goal is to produce personal responses, such as awareness, enjoyment, or interest in science. Science communicators seek novel ways of communicating with the public, often using new technologies to produce personal responses. Thus, we explored how mid-air haptics technology could play a role in communicating scientific concepts. We prototyped six mid-air haptic probes for three thematic areas: particle physics, quantum mechanics, cell biology; and conducted three qualitative focus group sessions with domain expert science communicators. Participants highlighted values of the dynamic features of mid-air haptics, its ability to produce shared experiences, and its flexibility in communicating scientific concepts through metaphors and stories. We discuss how mid-air haptics can complement existing approaches of science communication, for example multimedia experiences or live exhibits by helping to create enjoyment or interest, generalized to any fields of science.